2011IEEE 10th International Conference on Trust, Security and Privacy in Computing and Communications 2011
DOI: 10.1109/trustcom.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

A Scalability Study of AAA Support in Heterogeneous Networking Environments with Global Roaming Support

Abstract: Abstract-In this paper, we present a scalability study of AAA support in mobile heterogeneous access networks with respect to server and network load related to AAA processes using the RADIUS protocol. Technologies such as IEEE 802.11, CDMA 2000 and UMTS which all support the RADIUS protocol for AAA handling are discussed and analyzed. Typical performance data are gathered and complemented with a theoretical study in order to achieve an overview of what parameters will affect the performance and scalability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The reason is that LP-WAN networks look very similar to current cellular deployments, but with very limited resources. In fact, current wireless networks such as 3G, WiMAX or WiFi use, traditionally, AAA infrastructures to control the access to the network service at a large scale [ 15 , 16 , 17 ]. These infrastructures have been based on two main protocols: Remote Authentication Dial-In User Service (RADIUS) [ 18 ] or Diameter [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that LP-WAN networks look very similar to current cellular deployments, but with very limited resources. In fact, current wireless networks such as 3G, WiMAX or WiFi use, traditionally, AAA infrastructures to control the access to the network service at a large scale [ 15 , 16 , 17 ]. These infrastructures have been based on two main protocols: Remote Authentication Dial-In User Service (RADIUS) [ 18 ] or Diameter [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the performance bottleneck in the AAA system depends on, not only the authentication protocol used, but also the authentication delay as well as the number of entries in the user (or sensor) database. If the authentication is carried out using a lightweight authentication protocol such as EAP-Swift, it is likely that the network connection to the AAA server is saturated before the CPU is overloaded [ 48 ]. Likewise, if the authentication latency is very high, the server needs to keep RAM memory allocated for the authentication session during a longer time which may cause memory depletion [ 48 ].…”
Section: Results Analysismentioning
confidence: 99%
“…If the authentication is carried out using a lightweight authentication protocol such as EAP-Swift, it is likely that the network connection to the AAA server is saturated before the CPU is overloaded [ 48 ]. Likewise, if the authentication latency is very high, the server needs to keep RAM memory allocated for the authentication session during a longer time which may cause memory depletion [ 48 ]. The aforementioned factors are unlikely with EAP-Swift due to low CPU demand and fast authentications.…”
Section: Results Analysismentioning
confidence: 99%
“…Therefore, in our testbed, we implemented EAP-Swift as a FreeRadius plugin. Furthermore, results from a scalability study of the FreeRadius server [42] showed that the server is suitable for building highly scalable systems. …”
Section: Results Analysismentioning
confidence: 99%